2022
DOI: 10.1590/1806-9282.20210776
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the prenatal psychosocial profile with postpartum maternal duties and newborn care

Abstract: OBJECTIVE: This study aimed to determine the relationship of the prenatal psychosocial profile with postpartum maternity duties and newborn care. METHODS: This descriptive and correlational study was conducted on 154 pregnant women. RESULTS: It was determined that pregnant women had low-stress levels, high social support from their husbands and other people, and moderate self-esteem. Participants relying on power in coping with maternity duties in the postpartum period and satisfaction with maternity and newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The findings revealed that education and knowledge improved women's coping abilities. In line with this, a Turkish study of women's postpartum coping found that higher educational attainment improved women's coping abilities (Gunaydin and Zengin, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…The findings revealed that education and knowledge improved women's coping abilities. In line with this, a Turkish study of women's postpartum coping found that higher educational attainment improved women's coping abilities (Gunaydin and Zengin, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…The findings revealed that education and knowledge improved women's coping abilities. In line with this, a Turkish study on women's postpartum coping found that women and their husbands' educational level had a favorable impact on their coping abilities (Gunaydin & Zengin, 2022).…”
Section: Discussionmentioning
confidence: 72%
“…In the study conducted by Yüksel et al ( 19 ), those who had work-related distress or difficulties during pregnancy experienced more prenatal distress than those who did not. Günaydın et al ( 20 ) on the other hand, emphasized that working pregnant women received less social support from their environment and that they should be supported more. Our findings showed that women who had higher education levels and had a job experienced prenatal stress more intensely.…”
Section: Discussionmentioning
confidence: 99%